Personal and historical nostalgia: A comparison of common emotions - Phau, Ian; Marchegiani, Christopher (The Haworth Press Inc, 2013)
This research uses an experimental research design to examine differences in the emotional responses of 806 respondents experiencing specifically personal or historical nostalgic reactions to advertising appeals. Changes in intensity of five emotions common to both reactions are examined. Upbeat/elation, loss/regret, and warm/tender emotions are significantly heightened under the personal compared with the historical nostalgic response. Negative/irritation and serenity/calm-related emotions are not significantly different. These results highlight the need to examine nostalgia as two separate reactions and provide insights useful to practitioners regarding emotional reactions to each form. It also suggests the need for future research into personal and historical nostalgia’s comparable influences on other responses.